Measurements of Static Welfare Losses, Distribution Inequities, and Revenues in the Brazilian Multiple Auction Exchange Rate System - Huddle, Donald L. (Quarterly Journal of Economics, 1975)
I. Introduction, 490. — II. A brief description of the system, 491. — III. Static welfare losses from foreign exchange pricing, 491. — IV. Revenue gains and losses, 495. — V. Other costs and offsets, 498. — Appendix A: general method: converting loss estimates to linear estimates around the regression means, 499. — Appendix B: methodology of welfare loss calculations, 500.